Rhabdomyosarcoma in a terrestrial tortoise (Geochelone nigra) in Nigeria: a case report (2012)
A skeletal muscle tumour (rhabdomysarcoma) was diagnosed in a 4-year-old captive female terrestrial tortoise (Geochelone nigra) weighing 7kg presented at the Veterinary Teaching Hospital, University of Ibadan, Ibadan, Nigeria. The tumour was located at the anterior right portion of the body and ventral to the carapace. The location of the tumour prevented the tortoise from extending its head from the body. The tumour was a sessile, smooth white mass, with a soft myxomatous consistency. The histological features that were diagnostic of rhabdomyosarcoma included a sparse population of haphazardly arranged spindle-shaped cells within a homogenous matrix (anisocytosis), occasional tumour giant and binucleate cells, and some well differentiated myofibrils with cross striations within the cytoplasm. The paucity of information on tumours in the land tortoise was the reason for this report, which appears to be the first report of rhabdomyosarcoma in the tortoise